Screening of blackgram genotypes for molecular variability in reaction to Mungbean yellow mosaic disease - PH. SOBITA DEVI; BIRESWAR SINHA, H. CHANDRAJINI DEVI*, V. PRASANNA KUMARI (Indian Phytopathology, 2017)
Sixteen blackgram genotypes were tested for yellow mosaic disease under field conditions and identified nine genotypes as resistant, one as moderately resistant, four as susceptible and two as highly susceptible. No genotypes were found to be immune or highly resistant against yellow mosaic disease. Polymerase Chain reaction (PCR) of DNAs from sixteen genotypes using Sequence Characterized Amplified Region (SCAR) markers namely, SCAR 20F/20R resulted in specific amplification in nine genotypes indicating resistant nature of these genotypes. There was no amplification in six genotypes while faint amplification could be observed in the genotype LBG-752 that recorded 14.47% incidence of the disease along with moderately phenotypic reaction.